Evaluation of the Utilization of the Hospital Management Information System (SIMRS) at Madani Regional General Hospital, Palu - Muhammad Rifial; Amran Razak; Darmawansyah Darmawansyah; Indar Indar; Arsyad Rahman (Journal of Public Health and Pharmacy)
Introduction: The Hospital Management Information System (SIMRS) plays a crucial role in supporting optimal healthcare services in hospitals. SIMRS enables efficient and effective management of information, ranging from patient data to hospital administration. At Madani Regional General Hospital, Palu, the implementation of SIMRS has been carried out; however, operational challenges and user satisfaction issues still need to be evaluated. This study aims to evaluate the utilization of SIMRS at Madani Regional General Hospital, Palu, in 2024, and to analysed the impact of system usage, user satisfaction, information quality, and service quality on the net benefits of SIMRS.